Nitric Acid Promoted Metal-Free Bromothiolation of Internal Alkynes with Hydrobromic Acid and Disulfides - Sun, Han; Huang, Xiao-Cheng; Yao, Zhi-Xiang; Su, Hui (Synlett, 2022)
A novel, metal-free bromo-thiolation of internal alkynes with hydrobromic acid and disulfides has been developed. The reaction is promoted by commercial-grade nitric acid and is used to construct a series of unexplored β-bromoalkenyl sulfides in moderate to good yield. Most products were obtained with high stereoselectivity as syn-configured tetrasubstituted alkenes. Both sulfide groups of the disulfide reagent were used in this method.
Keywords: bromo-thiolation; internal alkynes; hydrobromic acid; disulfides; nitric acid; β-bromoalkenyl sulfides; syn-configuration